Competency Level of Private Secondary Science School Teachers of San Carlos City Division - Reyes, Milleohnes DG.; Catungal, Myra C. (Asian Journal of Multidisciplinary Studies, 2018)
This study sought to determine the competency level of Private Secondary Science School Teachers of San Carlos City Division during the School Year 2012-2013 to their teaching performance. The descriptive method of research was used in this study, with the questionnaire as the main instrument in gathering the data. This approach is appropriate wherever the object of any class varies among themselves, and one is interested in knowing the extent to which different conditions obtain among these objects. (Good and Scates1982). The descriptive-survey method is the most appropriate technique to employ mainly because it aimed to identify and analyze the level of competency of Private Secondary Science Schools Teachers in San Carlos City Division in Pangasinan. This design will be used by the researcher because it will describe and document aspects of a situation as it naturally occurs (Polit and Beck, 2008). It allows interpretation of what is and reveals the condition and relationship that exists or does not exist. An assortment of information was studied, analyzed, and documented to provide better bases, clarification and analysis of data. A survey questionnaire will be used and distributed to respondents from the Private Secondary Science Schools Teachers in San Carlos City. The goal of this study was to determine the competency level of private secondary science schools’ teachers in San Carlos City Division during the School Year 2013-2014. It also determines the different problems being encountered by the abovementioned respondents and also the proposed intervention plan that measures to address the needs identified directed towards enhancing the institutions’ level of competency on the private secondary science schools teachers in San Carlos City Division.in order to gather facts, the researcher made use of three-pronged questionnaire. This questionnaire was based on various readings from books and existing evaluation forms for faculty members of Virgen Milagrosa University Foundation. The questionnaire therefore, has adopted and modified some items, particularly that of teaching strategies and instructional materials from the reference books, the VMUF faculty evaluation form and online assessment rubrics. In effect, the present questionnaire is a modification of assessment items based on the above sources and has developed into a self-assessment rubric aimed at assessing one’s competence as a teacher.